Transformasi Dakwah Pesantren melalui Media Digital: Studi Kasus Pondok Pesantren Darussalam Blokagung Banyuwangi - Huda Al ihsan Huda, Rizqi; Obianto, Agung (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
The advancement of digital technology compels religious institutions, including Pondok Pesantren Darussalam Blokagung Banyuwangi, to adapt in delivering Islamic preaching in a more relevant and contextual manner. This study aims to examine the utilization of digital media in the pesantren's da'wah activities and to identify the challenges encountered in the process. Employing a descriptive qualitative method with a case study approach, data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, presentation, and conclusion drawing. The findings reveal that the pesantren has successfully integrated digital technology into its da'wah, particularly through platforms such as YouTube, Instagram, and TikTok. However, several challenges remain, including the spread of hoaxes, ethical issues in digital da'wah communication, and a technological skill gap among preachers. This study recommends enhancing digital literacy and providing technical training for preachers to ensure that Islamic messages remain relevant and ethically delivered in the digital age.